Case Report: Grade II Hypertension Accompanied by Obesity with Consumption of Propolis Herbs - Arsa, Sri Asmawati; Makmun, Armanto; Paulus, Paulus (Journal La Medihealtico, 2024)
Hypertension is often said to be a silent killer, because it is a deadly disease without being accompanied by symptoms first as a warning for the victim. Hypertension with the incidence of obesity is still common. The prevalence of hypertension accompanied by obesity also continues to increase. According to some studies, obesity and hypertension have a meaningful relationship. One alternative treatment that can be an option to lower blood pressure is herbal therapy. Herbal medicine is classified as complementary medicine is a phenomenon that appears today among many other non-conventional treatment phenomena, such as treatment with herbs or herbal therapy, acupuncture, and cupping. The use of herbs is one of the alternative treatments chosen by the community other than conventional (medical) treatment.One of the natural products produced is propolis. Propolis is one of the natural products produced by bees and is widely used as a medicine or supplement, anti-inflammatory, disease treatment, accelerating wound healing, and others. The patient in this case is a woman with the age of 50 years. Patients come with complaints of dizziness, headache and low back pain accompanied by a history of hypertension, and obesity. The patient was diagnosed with Grade 2 Hypertension on Treatment, and Obesity was given therapy in the form of Amlodipine 10 mg 1x1, Paracetamol 500 mg 3x1 and Vitamin B Complex 2x1.Hypertension suffered by patients is hypertension obtained due to several predisposing factors in patients, namely diet, obesity, age, and gender.